2015
DOI: 10.30537/sijmb.v2i1.86
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Inflation: Evidence from Pakistan using Autoregressive Distributed Lagged Approach

Abstract: Controlling inflation is one of the biggest challenges faced by the macroeconomic policymakers in Pakistan. This research article is aimed at highlighting the main sources of inflation in the economy of Pakistan using an autoregressive distributed lag model for the period from 1980 to 2012. Findings of this study reveal that the one percent rise in the long run money supply, exchange rate, total reserve, and the gross national expenditure change inflation by 0.16, 2.12, 0.36, and 1.78 percent points respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…At first, this technique is generally considered than Engle and Granger (1987) and Johansen (1991) when the sample size is small (Ghatak and Siddiki, 2001), whereas the Johansen's (1991) co-integration technique requires large sample data. Second, this technique can be applied whether the variables are integrated of order I (0) or I (1) (Chang et al, 2019;Anjum et al, 2017;Bhutto and Chang, 2019;Chang, Rajput and Ghumro, 2018;Ghumro and Karim, 2017;Ghumro and Memon, 2015). On the contrary other techniques such as VECM and VAR require that all variables should be integrated of the same order (Pesaran et al, 2001).…”
Section: Model Specification and Estimation Techniquesmentioning
confidence: 99%
“…At first, this technique is generally considered than Engle and Granger (1987) and Johansen (1991) when the sample size is small (Ghatak and Siddiki, 2001), whereas the Johansen's (1991) co-integration technique requires large sample data. Second, this technique can be applied whether the variables are integrated of order I (0) or I (1) (Chang et al, 2019;Anjum et al, 2017;Bhutto and Chang, 2019;Chang, Rajput and Ghumro, 2018;Ghumro and Karim, 2017;Ghumro and Memon, 2015). On the contrary other techniques such as VECM and VAR require that all variables should be integrated of the same order (Pesaran et al, 2001).…”
Section: Model Specification and Estimation Techniquesmentioning
confidence: 99%
“…The results showed that inflation and lagged inflation played a significant impact on domestic inflation in Pakistan. Ghumro and Memon (2018) investigated the determinants of inflation evidence from Pakistan. The study concluded that `broad money supply, the exchange rate, first lags in the domestic price level, GDP, gross national expenditures and total reserves considered the important determents of inflation in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Serilerin I(2) ikinci dereceden bütünlenen olmaması söz konusu yöntemin kullanılabilmesi için bir ön koşuldur. Çoğu kez seriler farklı dereceden bütünlenen oldukları için ARDL modelinin kullanılması uygundur (Chang vd., 2019;Anjum vd., 2017;Chang & Rajput, 2018;Ghumro & Memon, 2015). Diğer yandan gözlem sayısının az olduğu durumlarda da etkin ve tutarlı sonuçlar elde edilebilmektedir (Narayan & Narayan, 2004).…”
Section: Metodoloji Ve Bulgularunclassified